Application of the saw method for employee selection system in the PT Pinus Merah Abadi - Koeswara, Tya Septiani Nurfauzia; Marsusanti, Eva; Yulistria, Resti; Rosento, Rosento (Institute of Computer Science (IOCS), 2024)
PT Pinus Merah Abadi is a company engaged in the sales and distribution business with a distribution network spread throughout Indonesia, both through traditional and modern channels. Currently PT Pinus Merah Abadi carries out the employee selection process on average 2 (two) times a year with a total of 50-60 job applicants. The assessment process when selecting employees uses multiple criteria, namely assessment during psychological tests, competency tests and interviews. The employee selection process still has several problems, including subjectivity in the assessment process and it takes a long time because it is done manually, resulting in the decision making process being slow. Based on these problems, research is needed as a system innovation in making decisions regarding the selection or selection of new employees at PT Pinus Merah Abadi applies a simple additive weighting method based on six criteria, namely: test, education, age, experience, readiness and expertise. As a result, this system can help make it easier for HRD to select employees based on the highest ranking results.